FOLIAR APPLICATION OF NANO IRON OXIDE ENHANCES THE GROWTH, YIELD AND OIL CONTENT OF GROUNDNUT (Arachis hypogaea L.) IN CALCAREOUS VERTISOLS (Applied Biological Research, 2025)
Iron deficiency is a widespread nutritional problem, particularly in plants grown on calcareous and high pH soils. This study evaluated the impact of foliar application of nano iron oxide (Fe₂O₃ NPs) on the growth, yield attributes, and oil content of groundnut (Arachis hypogaea L.) under controlled pot culture conditions in a calcareous vertisol. Treatments included soil-applied ferrous sulphate, foliar-applied conventional ferrous sulphate, and various concentrations of nano-iron oxide (100 to 1500 ppm) applied 30 days after sowing. Among all treatments, foliar application of nano iron @ 1000 ppm recorded the best results, significantly enhancing dry matter production (69.37 g), root parameters, number of pods per plant (58.0), kernels per plant (89.33), pod dry weight (30.5 g/plant), kernel dry weight (23.2 g/plant), oil content (48.1%), oil yield (11.24 g/plant), and crude protein (26.75%). Yield improvement was 46% and 35% higher compared to the recommended practice and foliar FeSO₄ application, respectively. The control treatment showed the lowest performance in all parameters.
Keywords: Calcareous soils; groundnut; iron deficiency; nano-iron formulations; yield; oil content